2023
DOI: 10.3389/fmicb.2023.1114707
|View full text |Cite
|
Sign up to set email alerts
|

Biosensors for point-of-care testing and personalized monitoring of gastrointestinal microbiota

Abstract: The gastrointestinal (GI) microbiota is essential in maintaining human health. Alteration of the GI microbiota or gut microbiota (GM) from homeostasis (i.e., dysbiosis) is associated with several communicable and non-communicable diseases. Thus, it is crucial to constantly monitor the GM composition and host–microbe interactions in the GI tract since they could provide vital health information and indicate possible predispositions to various diseases. Pathogens in the GI tract must be detected early to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 108 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…Probiotics, particularly those containing Lacto bacillus and Bifidobacterium strains, have shown promising results in the treatment of H. pylori infection. Recent studies have reported that probiotics can improve H. pylori eradication rates and reduce treatment-related side effects [16]. Rifabutin is a broad-spectrum antibiotic that has shown promising results in the treatment of H. pylori infection, particularly in cases of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics, particularly those containing Lacto bacillus and Bifidobacterium strains, have shown promising results in the treatment of H. pylori infection. Recent studies have reported that probiotics can improve H. pylori eradication rates and reduce treatment-related side effects [16]. Rifabutin is a broad-spectrum antibiotic that has shown promising results in the treatment of H. pylori infection, particularly in cases of antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%